Understanding Sustainable Growth in Online Communities of Open-Source Software : Case: Open Core Business - Gutierrez Burboa, Luis (My University, 2021)
Online communities are crucial for the survival and success of companies using the open core model, as they rely on attracting developers to use their open-source software (OSS) and con-verting some of those free users into paying customers. Current research focuses on the success factors of OSS projects, motivations to contribute, and the sustained participation from the community perspective. This thesis provides the company’s point of view and adds the concept of sustainability to the growth of online communities, which makes this topic very relevant. The main objective of thesis is to uncover the characteristics of successful communities that propitiate sustainable growth, and what are the main challenges that stand in the way by finding answers to following questions, in the context of OSS. a) What is the nature and relevance of online communities of OSS? b) What are the main factors that drive sustainable growth in online communities of OSS? c) What are the barriers for sustainable growth in online communities of OSS? To achieve this understanding, the literature review widely covers the phenomenon of open-source software communities from what they are to why are they relevant, and how can the success of these online communities be measured. Finally, the current research on sustain-able growth in online communities and its success factors and barriers are covered. To expand the current knowledge on the sustainable growth of OSS communities, a case study is con-ducted by interviewing six key members that work with the community in an open core company by using the standardized open-ended interview approach and a six-phased thematic analysis. The findings of the study identify four areas to look after when planning for sustainable growth: member’s activities, communication platforms, company involvement, and product & marketing. Among the success factors, support, engagement, and recognition are brought up as some of the key drivers. On the other hand, the data suggests the main challenges are found in the form of communication barriers, inadequate resources, brand misconceptions, social issues, and challenges in product development.
Keywords: Online communities, OSS, open core, sustainable growth, community building, developers, OSS ecosystem, sense of community, engagement, support